My relationship with technology is not a solemn relationship: interview with Matías Umpierrez (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Matías Umpierrez is a multidisciplinary artist born in Argentina in the early 1980s, of Uruguayan parents, who produces works that dialogue with theater, cinema and the visual arts. In this interview, he discusses about his works in several countries around the world on projects that integrate information technologies with the daily lives of people in large cities.
Keywords: Theater; Technology; Hybrid language